دور الصناديق الوقفية في تحقیق التنمية المستدامة في أفغانستان: دراسة تحلیلیة استشرافیة في ضوء التجربة المالیزیة: The Role of WAQF Funds in Achieving Sustainable Development in Afghanistan: A forward-looking analytical study in Light of the Malaysian Experience - Abdul Salam Salim; Bouhedda Ghalia; Muhammad Amanullah (International Journal of Al-Turath In Islamic Wealth and Finance, 2024)
الملخص إنّ الوقف کنظام مالي واجتماعي یعدّ أحد روائع الحضارة الإسلامیة وابتکاراتها العظیمة وإنّه یجسد القیم الإسلامیة التي حقّقت لنظام الوقف مقاصده الشرعية وأهدافه الإنسانیة في كل المجالات التنموية. تحاول هذه الورقة البحثية تناول دراسة دور الصناديق الوقفية في تحقيق التنمية المستدامة في أفغانستان مراعيةً في ذلك بعض التجارب العالمية المعاصرة مثل التجربة الماليزية. وقد استخدمت الدراسة المنهج الکیفي استقراء وتحلیلاً فیما یتعلق بالتأصیل والضبط لمفهوم الصنادیق الوقفیة وما یتعلق به من القضایا في أبعادها الشرعیة والتنمیة المستدامة في ضوء المقاصد الشرعیة. وخصلت الدراسة إلى جملة من النتائج والتوصیات؛ ومن أهمها: 1) هناك علاقة بین الوقف والتنمیة المستدامة؛ حیث إنّ هناك تشابه في الأهداف الأساسیة للوقف والسمات العامة الممیزة للتنمیة المستدامة، کما أنّ للوقف أثر کبیر في تحقیق أهم جوانب التنمیة المستدامة سواء الاجتماعیة أو الاقتصادیة أو البيئیة؛ فعسى أن يحقق تأسيس الصناديق الوقفية أهم أهداف التنمية المستدامة في المجتمع الأفغاني. 2) تعتبر الصنادیق الوقفیة أداة حدیثة تساهم في إعادة دور الوقف في تحقیق التنمیة المستدامة، وذلك من خلال قدرتها على تعبئة الأموال الوقفیة والمحافظة علیها وتنمیتها من أجل دعم مختلف أبعاد التنمیة المستدامة. 3) وتوصیة الباحثین لتناول التجارب المعاصرة للوقف، بحثاً وتحلیلاً ونقداً، بما یضمن ممارسة الفعل الحضاري للوقف لغرض الاستفادة منها في التجارب الناشئة مثل أفغانستان. Abstract WAQF, as a financial and social system, is considered one of the masterpieces of Islamic civilization and its great innovations. It embodies Islamic values that have achieved the Maqasid Al- Shar’iah and humanistic goals of the WAQF system in all developmental fields. This research paper seeks to study the role of WAQF funds in achieving sustainable development in Afghanistan, taking into account some contemporary global experiences such as the Malaysian experience. The study used qualitative methodology in exploration and analysis regarding the grounding and adjustment of the concept of WAQF funds and related issues in their legal and sustainable development dimensions in light of the Maqasid Al- shari’ah. The study yielded a number of results and recommendations, including: 1) There is a relationship between WAQFs and sustainable development, as there is similarity in the fundamental goals of WAQFs and the general characteristics of sustainable development. WAQFs have a significant impact on achieving key aspects of sustainable development, whether social, economic, or environmental. Establishing WAQF funds may achieve key objectives of sustainable development in Afghan society. 2) WAQF funds are considered a modern tool that contributes to re-establishing the role of WAQFs in achieving sustainable development by mobilizing WAQF funds, and preserving and developing them to support various dimensions of sustainable development. 3) Researchers recommend studying contemporary WAQF experiences through research, analysis, and critique to ensure the cultural practice of WAQFs benefits emerging experiences like Afghanistan.